2005
DOI: 10.1007/bf02977797
|View full text |Cite
|
Sign up to set email alerts
|

Agastache rugosa leaf extract inhibits the iNOS expression in ROS 17/2.8 cells activated with TNF-α and IL-1β

Abstract: It has been suggested that nitric oxide (NO) derived from inducible nitric oxide synthase (iNOS) may act as a mediator of cytokine-induced effects on bone turn-over. NO is also recognized as an important factor in bone remodeling, i.e., participating in osteoblast apoptosis in an arthritic joint. The components of Agastache rugosa are known to have many pharmacological activities. In the present study, we investigated the effects of Agastache rugosa leaf extract (ELAR) on NO production and the iNOS expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Each of the components has been shown to have pharmacological activity in modulating the immune system and to have anti-inflammatory or antioxidant properties or both. [16][17][18][19][20][21][22] The purity of the KSY was evaluated by screening ingredients for contamination by heavy metals and pesticides and by a microbial limit test. Standard contents and quality control were analyzed by Internal Transcribed Space (ITS) technology and high-performance liquid chromatography (HPLC) at the Industrial Technology Research Institute, Hsinchu, Taiwan.We used ITS to analyze each of the 7 component ingredients in KSY to establish their DNA sequence, then analyzed the final KSY decoction using HPLC-PCA.…”
Section: Quality Control and Safety Of Ksymentioning
confidence: 99%
“…Each of the components has been shown to have pharmacological activity in modulating the immune system and to have anti-inflammatory or antioxidant properties or both. [16][17][18][19][20][21][22] The purity of the KSY was evaluated by screening ingredients for contamination by heavy metals and pesticides and by a microbial limit test. Standard contents and quality control were analyzed by Internal Transcribed Space (ITS) technology and high-performance liquid chromatography (HPLC) at the Industrial Technology Research Institute, Hsinchu, Taiwan.We used ITS to analyze each of the 7 component ingredients in KSY to establish their DNA sequence, then analyzed the final KSY decoction using HPLC-PCA.…”
Section: Quality Control and Safety Of Ksymentioning
confidence: 99%
“…It is used in Chinese traditional medicine for the treatment of cholera, vomiting, and miasma, and has been reported to have antitumor, antifungal, antiatherogenic and cytotoxic activities (Oh et al 2005;Shin and Kang 2003;Hong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have shown that Codonopsis pilosula, Atractylodes macrocephala, Poria cocos, Glycyrrhiza, Radix astragali, Agastachis herba, and Fructus ligustri have the potential to modulate the immune system, with antiinflammatory and antioxidant properties. [17][18][19][20][21][22][23] Thus, KSY might have the potential to improve liver function through immune modulation, with anti-inflammation and antioxidant properties. The details of the mechanism must be further explored in the future.…”
Section: Discussionmentioning
confidence: 98%